Distribution characteristics of ABO and RhD blood groups among the voluntary blood donors in Chongqing: A retrospective study. Issue 42 (16th October 2020) - Liao, Hongmei; Li, Jun
Abstract : Abstract: The distribution characteristics of ABO and RhD blood groups in the world were different and the data were limited. The aim was to investigate the distribution characteristics of ABO and RhD blood groups in Chongqing, and to provide scientific-effective data for a more reasonable blood collection program. We retrospectively analyzed 795 698 blood donors who had donated blood from 2014 to 2019 at the Chongqing Blood Center. The data on ABO and RhD blood groups were extracted based on blood management system. We used percentages to describe the extraction of data on blood donors by gender, age, and nationality. The data on the distribution of ABO (A, B, AB and O) and RhD (RhD-Positive and RhD-Negative) blood groups were reported also in percentages. Of those, 427 516 (53.73%) were males and 368 182 (46.27%) were females. Among all the blood donors, 321 916 (40.46%) were under the age of 25, followed by 26–35 years age group (22.65%), 36-45 years age group (18.95%), 46-55 years age group (16.98%) and 56-60 years age group (0.96%). There were 755439 (94.94%) of the blood donors who were of the Han nationality. The distribution of blood groups O, A, B and AB were 35.54%, 31.90%, 24.14% and 8.42%, respectively. The distributions of RhD-Negative group was found in 4362 (0.55%) blood donors. The distribution characteristics of the ABO and RhD blood group should be considered when improving blood collection program in Chongqing.